DAYA SAING KOMODITAS KELAPA INDONESIA DAN PRODUK TURUNANNYA - Syahrul Ganda Sukmaya; Atika Dyah Perwita (UPT Penerbitan Universitas Jember, 2018)
In this era of of free trade ensuring every country compete for contracts as they to indonesia to offer new her products to the market in order to obtain some international bank indonesia foreign exchange .Agricultural products being specific the location of an impact of on the development of a superior products traded with anything quot on the international market .A genus of plants kelapa it can grow in both indonesia because it was permanently connecting the pole pieces located within close proximity of interests in the matter and of course are suitable for grow and the expansion of the methods for cashew nut trees .This situation has made indonesia has certain excellence in commodities kelapa , this can be seen from the production of kelapa indonesia abundance of his riches seeking and it is automatically become one of the producers kelapa largest in the world .For that reason it is , this research identify the competitiveness of from products of coconut and of its derivatives to make it capable in examine the potential market coconut product gdp figures last week and its down stream actvities benefit the development of these commodities only require showed indonesia exports. To see competitiveness used RCA (Revealed Comparative Analysis) , RSCA (Revealed Symetric Comparative Advantage ) and CMS ( Constant Market to Share). The RCA and RSCA used to compare the competitiveness of commodities and derivatives oil exporters compared to the other and CMS oil exporting of commodities used for growth and by products. Based on the results show that commodities coconut and by products have competitiveness in the global market and the exporting of commodities is influenced by the effects of global import growth in effect a composition